2016
DOI: 10.1007/s00404-016-4108-8
|View full text |Cite
|
Sign up to set email alerts
|

Review and meta-analysis of prospective randomized controlled trials (RCTs) comparing laparo-endoscopic single site and multiport laparoscopy in gynecologic operative procedures

Abstract: LESS may be considered an alternative to MPL with comparable feasibility and safety in gynecologic operative procedures. However, it does not offer the expected advantages in terms of postoperative pain and cosmetic satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…In the LESS approach, no additional port was needed. In other trials, a frequency of 3.5% to additional port was denoted [17]. Our results demonstrated that LESS hysterectomy was comparable to conventional laparoscopic hysterectomy, mainly depending on the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 51%
“…In the LESS approach, no additional port was needed. In other trials, a frequency of 3.5% to additional port was denoted [17]. Our results demonstrated that LESS hysterectomy was comparable to conventional laparoscopic hysterectomy, mainly depending on the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 51%
“…Since LESS requires only a single incision in the umbilicus, some authors advocate that it is associated with a better cosmetic outcome compared with conventional laparoscopy [12, 24, 25]. We were unable to evaluate this variable among the selected studies since this information was not reported.…”
Section: Discussionmentioning
confidence: 79%
“…However, only recently it has gained popularity and has been adopted in several fields including gynecology [12]. This is mainly related to the advances in technological innovation with the introduction of multi-channel single port systems and articulating instruments.…”
Section: Introductionmentioning
confidence: 99%
“…If the flexible scope is to be used, the tip of the scope can be adjusted to the center of the surgical field without moving the straight segment to provide adequate triangulation and avoid clashing with the surgeon's instruments. 19 Left pelvic side wall adhesions were be released from the lateral pelvic wall using flexible or conventional laparoscopic shears (Cambridge Endo, Framingham, MA), which help to improve the surgical range of motion to reach extreme angles in the pelvis. 20 We then grasped the tubes and ovaries, brought them through the multichannel port after detaching all the trocars from the abdomen.…”
Section: Methodsmentioning
confidence: 99%
“…The left ureter can be more difficult to find because it is often covered by the base of the sigmoid mesocolon. 19 Many time anatomic landmarks are distorted by adhesions endometriosis, or prior surgical exploration. In those cases dissection started from the most normal area and then it should proceed toward the more distorted parts of the operative field.…”
Section: Methodsmentioning
confidence: 99%